Experimental investigation of flow field features and spark ignition process in a multi-swirl airblast injector. (15th December 2021) - Zhao, Qianpeng; Yang, Jinhu; Mu, Yong; Li, Yao; Liu, Cunxi; Liu, Fuqiang; Wang, Shaolin; Xu, Gang
Highlights: The effects of flow field structure and droplets distribution on flame propagation. The trajectory processing algorithm for identifying flame propagation behaviors. The flame propagation patterns in successful and misfire scenarios. The flow field features and flame evolution under different pressure drops. Abstract: Lean combustion has been applied in aero gas turbine engines in response to rising concerns regarding the effects of pollutant emissions on the environment. As one of low emissions combustion technologies, stratified partially premixed combustion is capable of reducing NOx emissions while still providing robust pilot flames. In this work, the processes of liquid fuel atomization, fuel–air mixing and spark ignition in a multi-swirl staged combustor with airblast atomizer are experimentally investigated to further illustrate the effects of flow field features on flame propagation and the underlying reasons leading to successful and failed ignitions (misfires). A trajectory processing algorithm is developed to identify the detailed flame propagation behaviors in successful and misfire scenarios. PIV, PMie and High-speed imaging technologies are applied to provide the velocity distribution, droplets distribution and time-resolved flame images, respectively. Evolution of projected flames shows that the mechanism of flame motions in the early phase following spark can be explained by non-reacting flow structures and spray distributions. It is demonstrated that the early phase propagating trajectories play an important role in determining overall successful ignition. The variation regarding the flow field, droplets distribution, and flame evolution under pressure drops varying from 1% to 6% are analyzed. The ignition and combustion reach a relatively stable state when the pressure drop of injector exceeds 4%, which reflects in the minimum LLO FAR varies around 0.021 ± 0.001 and the time of flame development stabilizes at 40 ± 5 ms.